Tomato spotted wilt virus in tomato from Croatia, Montenegro and Slovenia: genetic diversity and evolution - Dijana Škorić; Jelena Zindović; Dorotea Grbin; Patrik Pul; Vladan Božović; Paolo Margaria; Nataša Mehle; Nataša Mehle; Anja Pecman; Zala Kogej Zwitter; Zala Kogej Zwitter; Denis Kutnjak; et al. (Frontiers in Microbiology)
Tomato spotted wilt orthotospovirus (TSWV) is a major plant pathogen causing significant economic losses in tomato production worldwide. Understanding its genetic diversity and evolutionary mechanisms is crucial for effective disease management. This study analyzed TSWV isolates from symptomatic tomato plants collected across Croatia, Montenegro and Slovenia between 2020 and 2024. High-throughput sequencing (HTS) was employed to obtain whole-genome sequences, followed by phylogenetic analyses to assess genetic variability and relationships among isolates from these three countries and other isolates of worldwide geographic origin. Phylogenetic analyses placed all studied isolates within the L1-M3-S3 genotype, commonly associated with solanaceous crops in Europe. While Croatian and Slovenian isolates exhibited high genetic similarity, Montenegrin isolates clustered in a distinct subgroup, showing closer relationships to Asian and Mediterranean accessions. Despite the severe disease symptoms observed, no substitutions in the NSm protein associated with resistance-breaking (RB) phenotypes were detected. These findings suggest that additional virome components, environmental factors or so far unknown mechanism(s) may contribute to infection and disease severity in tomato and strongly support the need of continuous surveillance of TSWV genetic diversity in order to inform breeding programs and develop sustainable management strategies to mitigate future outbreaks.